2009
DOI: 10.1007/s11099-009-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Can the Giberella zeae toxin zearalenone affect the photosynthetic productivity and increase yield formation in spring wheat and soybean plants?

Abstract: The seeds of soybean cv. Aldana and spring wheat cv. Torka were soaked for 24 h in solution of zearalenone [ZEN, 2,4-dihydroxy-6-(10-hydroxy-6-oxo-trans-1-undecenyl)-benzonic acid lactone, 4 mg dm -3 ] and then they were sown in the pot experiment in an open vegetation hall. The after-effects of ZEN on growth of plants, net photosynthetic (P N ) and transpiration (E) rates, stomatal conductance (g s ), photochemical efficiency of photosystem II (PSII) and on final seeds yield, were determined. A significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The increase in photochemical activity of PSII in soybean seedlings after soaking of seeds in ZEN solutions (Table 3) proved similar to that in leaf discs incubated in ZEN solutions. These results are consistent with the earlier observations (Kościelniak et al 2009) that ZEN treatment of plants was the resulted increase in photochemical activity of PSII at the early developmental stages in soybean. ZEN inhibited photochemical reactions in wheat discs, but did not affect PSII activity in wheat seedlings.…”
Section: Photochemical Activity Of Psiisupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in photochemical activity of PSII in soybean seedlings after soaking of seeds in ZEN solutions (Table 3) proved similar to that in leaf discs incubated in ZEN solutions. These results are consistent with the earlier observations (Kościelniak et al 2009) that ZEN treatment of plants was the resulted increase in photochemical activity of PSII at the early developmental stages in soybean. ZEN inhibited photochemical reactions in wheat discs, but did not affect PSII activity in wheat seedlings.…”
Section: Photochemical Activity Of Psiisupporting
confidence: 93%
“…Studies revealed that ZEN induces reactions at many levels of animal cell organization (Hassen et al 2007). It was revealed that ZEN can be also toxic for plants causing chromosome damages and disorders in the synthesis of photosynthetic pigments (Kumar and Sinha 1995) as well as in photosynthesis and growth processes (Kościelniak et al 2009). On the other hand, it was found that ZEN was an endogenous regulator controlling plant development (Meng et al 1992), but as yet the mechanism of its action has not been explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In drought conditions, ZEN reduced absorbed energy flux (ABS) and trapped energy flux (TRo) for single PSII reaction centers (RCs) while maintaining the level of the electron transport per active reaction center (ETo/RC) at the level of control plants. This demonstrates the more efficient use of energy for photochemical processes in drought stress in plants treated Koscielniak et al (2009) showed that pre-sowing soaking of soybean and wheat seeds in ZEN solution caused a higher PSII efficiency under salt stress and, as a result, an increase in their yield. However, scarce data available in the literature indicate that the stimulation of the photosynthetic process by ZEN probably does not occur in all species.…”
Section: Discussionmentioning
confidence: 78%